Exposure to green space and prevention of anxiety and depression among young people in urban settings: a global scoping review. Issue 2 (28th May 2021) - Reece, Rebecca; Bray, Isabelle; Sinnett, Danielle; Hayward, Robert; Martin, Faith
Abstract : Purpose: There is a mental health crisis, particularly among young people. Despite many young people living in urban settings, reviews about the association between exposure to green or natural environments and mental health tend to focus on either children or adults. The aim of this review is to examine the scope of the global literature for this age group, to inform a systematic review on the role of exposure to green space in preventing anxiety and depression amongst young people aged 14–24 years. Design/methodology/approach: Seven databases were searched for quantitative and qualitative sources published from January 2000 to June 2020. This identified 201 sources and their characteristics are described here. Gaps in the literature are also highlighted. Findings: The number of relevant studies published per year has increased over time. Most studies are set in North America (28%) or Europe (39%). The most common study designs were observational (34%) or experimental (28%). A wide range of exposures and interventions are described. Research limitations/implications: This review included literature from predominantly high-income countries and has shown the under-representation of low-middle income countries and lack of ethnic diversity in study populations. It has also highlighted the lack of clinical measures of anxiety and depression as outcomes. Originality/value: This inter-disciplinary review has contributed to the field by describing the geographic distribution of the literature and the broad range of exposures to green spaces being reported. Unlike previous scoping reviews, this review focused specifically on young people and on measures of anxiety and depression and their pre-cursers.